Photocatalytic and Antimicrobial Performance Evaluation of Reusable MoS2 Nanoflowers under Visible Light - Senthilnathan Selvaraj; Mathew K. Francis; P. Balaji Bhargav; Nafis Ahmed (ECS Advances, 2023)
2D semiconductor material, Molybdenum Disulfide (MoS _2 ), with unique properties similar to that of graphene, is considered as a potential candidate for photocatalytic and antimicrobial applications. In the current work, MoS _2 was prepared by a simple hydrothermal method using sodium molybdate and thiourea as precursors. The calculated band gap values of MoS _2 grown at 200 °C and 180 °C were 2.1 eV and 1.98 eV, respectively. Flower like morphology was observed from FESEM analysis. Multi layered structure of MoS _2 was confirmed from the difference the peak value obtained for A _1g and E ^1 _2g vibrational modes observed from Raman spectra. The reusability of the synthesized MoS _2 was analyzed against MB dye degradation. The pristine MoS _2 removed ∼98% of the dye molecules from the water under the minimum wattage (20 W) of visible light in 180 min. The catalyst retained good stability even after the third degradation, confirming the reusability of MoS _2 . The disk diffusion method was used to evaluate the antimicrobial activity of the grown MoS _2 nanostructures. The gram-positive and gram-negative bacteria used in present study were Staphylococcus aureus, Klebsiella pneumoniae, Escherichia coli and Bacillus serius . Investigation of the antibacterial activity of MoS _2 against these four different pathogens was carried out in detail and the resistance function was measured.